Epistemic modal verbs in translation - Košař, Pavel (2007)
The subject of the dissertation is an analysis of translations of epistemic modal verbs. It is based on a parallel English-Czech corpus. The aim was to analyze how the Czech translator deals with the English epistemic modal verb. It mainly concentrates on the semantics of the source and target language texts. The starting point of the thesis is a theoretical description of modal verbs in English. The first chapter deals briefly with modality in general. It further concentrates on epistemic modality. The second chapter is devoted to the corpus used for the research and briefly to corpora in general. The third chapter contains some comments on the method used during the analysis, several general observations of the differences between source and target texts from the point of view of modality, general statistics of the frequency of occurrence of the analysed modal verbs and the analysis itself